Associations Between Physical Distancing and Mental Health, Sexual Health and Technology Use Among Gay, Bisexual and Other Men Who Have Sex With Men During the COVID-19 Pandemic. Issue 4 (21st March 2021) - Holloway, Ian W.; Garner, Alex; Tan, Diane; Ochoa, Ayako Miyashita; Santos, Glen Milo; Howell, Sean
ABSTRACT: Physical distancing measures, designed to limit the spread of COVID-19, have been implemented globally. We sought to understand how physical distancing impacts gay, bisexual and other men who have sex with men (GBMSM), a group disproportionately affected by poor health outcomes. A cross-sectional online survey on Hornet, a networking application (N = 10, 079), measured sociodemographics, physical distancing, mental health outcomes, and sexual behavior. Nearly two-thirds of participants (63%) reported only leaving their home for essentials. Those who practiced physical distancing were more likely to feel anxious (aOR = 1.37), feel lonely (aOR = 1.36), to report their sex life being impacted (aOR = 2.95), and less likely to be satisfied with their current sex life (aOR = 0.76). Those who practiced physical distancing were more likely to use social technologies to stay in touch with others. Risk reduction and telehealth opportunities may alleviate health challenges for GBMSM in the COVID-19 era.